Estimado a influência da taxa de câmbio sobre os fluxos de comércio exterior Brasileiros - Flavio Lyrio Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This study aims to analyze empirically the interactions between exchange rate behavior and the performance of Brazilian foreign trade. First, the empirical literature on the subject is reviewed, in order to elucidate methodological issues such as appropriate model type, identification strategy, explanatory variables and functional relationships. The effects of relative prices on foreign trade flows are then analyzed by estimating models of demand for imports and supply and demand for exports, both aggregated and disaggregated, for the period 1996-2012. The existence of cointegration is tested by the Engle-Granger procedure, and models are estimated by the fully modified least-squares method (FM-OLS). Among the main conclusions offered by the empirical analysis, it is noteworthy that in almost all of the estimated models, the effect of changes in the real exchange rate on Brazilian foreign trade flows is relatively modest. The domestic demand for imports seems to be mainly determined by income behavior, while demand for Brazilian exports is mainly drived by foreign income behavior - except in manufactured goods, for which the relative-price effect was more relevant. The supply of exports appears to be driven mainly by domestic productive capacity, with little influence of the real exchange rate.
Keywords: F10; F31; 330; exchange rates; foreign trade; exports; imports; elasticities